Algoritma Monte Carlo Dalam Penentuan Distribusi Pengguna Jaringan Di Kota Pekanbaru (Studi Kasus : LTE Multi-RAT GSM) - Seprita Wulansari; Linna Oktaviana Sari (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
LTE as the top cellular technology at this time has become the reference standard for the success of a user to connect the network. LTE planning with the Multi-RAT access system can optimize the planning of the 700 MHz LTE spectrum in Pekanbaru in the future. Multi-RAT is a technology planning for two or more RAT networks with a shared access system that can improve network performance. Based on the results of network to tracking using Nperf Software, there are many blankspot areas existing condition of Pekanbaru at this time can be said that causes users can not access the cellular network. To validate the success of the users side that connected to the network, then a Monte Carlo algorithm simulation that is run using Radio Planning Atoll Software is needed. Monte Carlo simulation is a probability simulation that analyzes network capacity using a user distribution to test the reliability of network coverage based on a randomization process.The data generated from the Monte Carlo algorithm simulation is connected user persentation and the value of throughput obtained from multiplication of single user throughput with number of active customers. In simulation testing to resulted Multi-RAT connected user is 99.93% of users with a throughput average around 2.968,72 Mbps. On the other side non Multi-RAT connected user is 97.83% of users connected with throughput average obtained at 2,198.1 Mbps. So, it can be concluded that LTE network planning with Multi-RAT technology can be taken into considered for future LTE planning because it produce higher percentage of average value of connected users and throughput.Keywords: LTE, Multi-RAT, Monte Carlo Algorithm Simulation, Connected UserThroughput Value.